Predictors of secondary school teachers’ use of information and communication technology in Akwa Ibom State, Nigeria - Uyouku, Arit Uyouko (2015)
This correlational study was to investigate the extent of ICT use and its relationship with attitudes, perceived ease of use, perceived usefulness, facilitating conditions and cultural perception among secondary school teachers in Akwa Ibom State of Nigeria. It also sought to determine the presence and non-presence of the conditions that facilitate ICT use among secondary school teachers. In addition, the study determined if teachers’ attitude, perceived ease of use, perceive usefulness, facilitating conditions and cultural perception are predictors of ICT use. The study added a qualitative element to the design with an interview session. Data were collected from the target population of teachers in all 232 government secondary schools (N=6927) in the three senatorial districts of the state. A stratified random sample of 386 teachers was selected and a set of questionnaires distributed. The reliability testing yielded an acceptable internal consistency of .75, descriptive statistics were employed to describe and summarize the attributes of the collection of data from respondents, Pearson’s Product Moment coefficient was to determine the relationship between individual independent variable of the study and the extent of ICT use by teachers. Also, multiple regressions was used to measure the proportion of the variance in ICT use by the independent variables and to identify the relative significance of each in explaining the dependent variable ICT use, the quantitative stage was followed up by an in-depth phone interviews with 10 teachers. Findings in this study indicated that almost half of the teachers had never used ICT in class to conduct classroom activities, suggesting that teachers’ ICT use was not evenly spread across schools, even as teachers highlighted the benefits of ICT use. Teachers held positive attitude towards ICT use and seemed to support and endorse its advantages over the “talk and chalk” method of teaching, though there was lack of ICT availability and accessibility. Findings in this study also indicated that teachers who agree to the presence and adequacy of facilitating conditions will use ICT for teaching and learning. Teachers’ cultural perception concern was more on inappropriate postings on some internet sites that they acknowledge were not suitable to the Nigerian culture. The study results revealed that teachers’ responses were relatively mixed in their opinion on cultural perception towards ICT use in Nigerian society and schools. Four variables (attitude, knowledge and skill, cultural perception and resources) were found to be significant predictors of ICT use by teachers. More than half of the variance (61%) in ICT use was explained by the aforesaid variables for teachers’ ICT use in teaching and learning.